The Effect of Digital Big Book Media on Early Reading Ability Among Elementary School Students - Rosmalah; Muliadi; Alifah Nur Alfiyyah (Journal of Primary Education Innovation and Research, 2025)
This study aims to determine the effect of Digital Big Book media on the early reading ability of Grade II students at SD Negeri 41 Mallari, Kabupaten Bone. This study used a quantitative approach with a pre-experimental research design. The research design applied was the One Group Pretest-Posttest Design. The independent variable was Digital Big Book media, while the dependent variable was students’ early reading ability. The population of this study consisted of all Grade II students at SD Negeri 41 Mallari, and the sample included 19 students selected using saturated sampling. Data were collected through an early reading ability test administered before and after the treatment. The data were analyzed using descriptive statistical analysis and inferential statistical analysis with the assistance of IBM SPSS Statistics version 25. The results showed that students’ pretest mean score was 48.68, which was categorized as fair. After three learning sessions using Digital Big Book media, the posttest mean score increased to 73.68, which was categorized as good. The normality test showed that the pretest and posttest data were normally distributed, while the homogeneity test showed that the data had homogeneous variance. The paired sample t-test showed that the tcount value was 16.882, which was higher than the t-table value of 1.73406. Therefore, the alternative hypothesis was accepted and the null hypothesis was rejected. These findings indicate that the use of Digital Big Book media has a significant effect on improving students’ early reading ability. Thus, Digital Big Book media can be used as an alternative learning medium to make early reading instruction more attractive, interactive, and meaningful for lowergrade elementary school students.